Implementing Self-Management Strategies to Reduce Truancy Behavior: A Qualitative Study in Islamic Junior Secondary Education - M. Firgiawan Kasman; Mardi Takwim; Hilal Mahmud (International Journal of Educational Administration, Management, and Leadership, 2024)
This study concludes that the implementation of self-management strategies at MTs Al-Mawasir Padang Kalua constitutes a systematic and effective approach to reducing truancy behavior through the integration of goal setting, self-monitoring, self-evaluation, and reinforcement processes. These stages enable students to develop self-regulation, responsibility, and behavioral awareness, indicating a shift from externally imposed discipline toward internally driven control. The findings also reveal that successful implementation is not solely dependent on individual student effort but is strongly influenced by institutional support, including teacher guidance, counseling services, and collaborative school structures. However, several challenges—such as low student motivation, limited family support, and structural constraints within the school—highlight that self-management requires both internal readiness and external reinforcement to function optimally. Therefore, this study affirms that self-management represents a strategic and sustainable intervention for addressing truancy, provided that it is implemented through a comprehensive framework that integrates behavioral, motivational, and environmental dimensions within the educational context.